More Than Just a Removal Service: Scavenger Receptors in Leukocyte Trafficking - Patten, Daniel A.; Shetty, Shishir (Frontiers in Immunology, 2018)
Scavenger receptors are a highly diverse superfamily of proteins which are grouped by their inherent ability to bind and internalise a wide array of structurally diverse ligands which can be either endogenous or exogenous in nature. Consequently, scavenger receptors are known to play important roles in host homeostasis, with common endogenous ligands including apoptotic cells and modified low density lipoproteins (LDLs); additionally, scavenger receptors are key regulators of inflammatory diseases, such as atherosclerosis. Also, as a consequence of their affinity for a wide range of microbial products, their role in innate immunity is also being increasingly studied. However, in this review, a secondary function of a number of endothelial-expressed scavenger receptors is discussed. There is increasing evidence that some endothelial-expressed scavenger receptors are able to directly bind leukocyte-expressed ligands and subsequently act as adhesion molecules in the trafficking of leukocytes in lymphatic and vascular tissues. Here, I cover the current literature on this alternative role for endothelial-expressed scavenger receptors and also speculate on their therapeutic potential.